2005
DOI: 10.1161/01.str.0000177495.45580.f1
|View full text |Cite
|
Sign up to set email alerts
|

Is Prehypertension a Risk Factor for Cardiovascular Diseases?

Abstract: Background and Purpose-The Joint National Committee on High Blood Pressure identified a new category of blood pressure in adults termed prehypertension. Our objective was to determine the long-term risk of cardiovascular diseases associated with this new category in a well-defined cohort of adults. Methods-We evaluated the association of prehypertension (120 to 139/80 to 89 mm Hg) and hypertension (Ͼ140/ 90 mm Hg) with the incidence of atherothrombotic brain infarction (ABI), all strokes, myocardial infarction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
177
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(186 citation statements)
references
References 21 publications
5
177
0
4
Order By: Relevance
“…Although these values are not suggestive of hypertension, the mean baseline SBP (135 mmHg) satisfies the criteria of systolic pre-hypertension [27] that is known to increase the risk of cardiovascular diseases [28]. Our finding is in agreement with epidemiological studies [12] and supports the hypothesis of a tendency toward hypertension in RLS.…”
Section: Discussionsupporting
confidence: 88%
“…Although these values are not suggestive of hypertension, the mean baseline SBP (135 mmHg) satisfies the criteria of systolic pre-hypertension [27] that is known to increase the risk of cardiovascular diseases [28]. Our finding is in agreement with epidemiological studies [12] and supports the hypothesis of a tendency toward hypertension in RLS.…”
Section: Discussionsupporting
confidence: 88%
“…10 This assumption is corroborated by the findings in a prospective study involving more than 5000 subjects where those with prehypertension had an increased risk of coronary heart disease and myocardial infarction which was related to SBP level but not with diastolic. 11 Another study using ABPM showed that NT subjects with endothelial dysfunction presented a higher 24-h blood pressure values, which is the reflex of consistent changes in the organisation of blood pressure circadian pattern probably related to vasopressor effects even in NT subjects. 12 There are some aspects that should be mentioned such as the impact of haemodynamic forces on arterial wall leading to damage and earlier atherosclerotic process that may be detected even in NT subjects, genetic predisposition and metabolic profile, which may individually or in association, play a role in the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 95%
“…1 The primary prevention of hypertension has been promoted to the population, particularly in adults with prehypertension (defined as systolic blood pressure (BP) of 120-139 mm Hg and/or diastolic BP of 80-89 mm Hg), 1 which is associated with an increase in cardiovascular morbidity and mortality. [2][3][4] Lifestyle modifications, including regular physical activity (PA), are the only recommended treatment for prehypertension. 1,5 The PA recommendation for the treatment of both prehypertension and hypertension includes the accumulation of 30 min or more of moderately intense PA in most, preferably all, days of the week.…”
Section: Introductionmentioning
confidence: 99%